Differences in DNA Methylation Between Disease-Resistant and Disease-Susceptible Chinese Tongue Sole (Cynoglossus semilaevis) Families - Xiu, Yunji; Shao, Changwei; Zhu, Ying; Li, Yangzhen; Gan, Tian; Xu, Wenteng; Piferrer, Francesc; Chen, Songlin (Frontiers in Genetics, 2019)
DNA methylation, the most widely studied and most well-understood epigenetic modification, has been reported to play crucial roles in diverse processes. Although it has been found that DNA methylation can modulate the expression of immune-related genes in teleosts, a systemic analysis of epigenetic regulation on teleost immunity has rarely been performed. In this research, we employed whole-genome bisulfite sequencing (WGBS) to investigate the genome-wide DNA methylation profiles in select disease-resistant Cynoglossus semilaevis (DR-CS, family 14L006) and disease-susceptible C. semilaevis (DS-CS, family 14L104) against Vibrio harveyi infection. The results showed that following selective breeding, DR-CS had higher DNA methylation levels and different DNA methylation patterns, with 3311 differentially methylated regions (DMRs) and 6456 differentially methylated genes (DMGs). Combining these data with the corresponding transcriptome data, we identified several immune-related genes that exhibited differential expression levels that were modulated by DNA methylation. Specifically, DNA methylation of tumor necrosis factor-like (TNF-like) and lipopolysaccharide-binding protein-like (LBP-like) was significantly correlated with their expression and significantly contributed to the disease resistance of the selected C. semilaevis family. In conclusion, we suggest that artificial selection for disease resistance in Chinese tongue sole causes changes in DNA methylation levels in important immune-related genes and that these epigenetic changes are potentially involved in multiple immune responses in Chinese tongue sole.